Selecting the Parameters of The Diagnosis of Frame Insulation Condition in Electrical Machines of Locomotives - Kapitsa, Michail; Laguta, Vasiliy; Kozik, Yuriy (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the signs displaying the insulation ageing process and allow predicting the change in its technical condition under operation of traction motors in locomotives. In order to choose the indicators of the insulation condition, the methods of linear electrical circuits were used to analyze the equivalent scheme of frame insulation. In the equivalent scheme, the dielectric micro- and macro-heterogeneities were taken into account. The most informative parameters of the frame insulation ageing process are those related to absorption and resorption processes over time. The return voltage has been selected as the main characteristic to determine the indicators of insulation condition. The analytical dependences for determining the frame insulation condition indicators have been obtained different from those currently used in the diagnosis of electrical machines. The choice of indicators will allow predicting changes in the technical condition of frame insulation in operation. The studies will allow us to change the regular preventive maintenance technology to the maintenance based on the facility condition. Â Â